Penerapan Teknologi Pompa Hidram bagi Masyarakat Pedesaan - Heri Zulfiar, Muhammad (Universitas Muhammadiyah Yogyakarta, 2020)
Water pump is a highly needed tool by society in providing clean water and irrigation. Generally, water pump used by the society is powered by electricity that requires cost to operate. This condition is also faced by the community of Serut hamlet, Palbapang, Bantul, while its area is filled by abundant water resources. Therefore, an alternative water pump requiring no cost to operate is highly needed. Hydram pump technology powered by water (renewable energy source) was offered as the alternative solution. Introducing hydram pump technology in Serut hamlet was done using socialization and education method and approach. The training and practice were done in the application of hydram pump technology. The program was appreciated by the community of Serut hamlet shown by their good understanding and good application of hydram pump technology.